Concanavalin-A Shows Synergistic Cytotoxicity with Tamoxifen via Inducing Apoptosis in Estrogen Receptor-Positive Breast Cancer: In Vitro and Molecular Docking Studies - Mohamed Elshal; Norhan Eid; Ibrahim El-Sayed; Wael El-Sayed; Ahmed Ali Al-Karmalawy (Tabriz University of Medical Sciences, 2022)
Background: Tamoxifen (TAM) is the main treatment of estrogen receptor (ER)-positive breast cancer, however; its adverse effects and development of resistance hinder its use. Concanavalin A (Con A) is a mannose/glucose-binding lectin that has been reported to induce apoptosis in a variety of cell lines. Methods: The effects of Con A on TAM-induced cell death in ERα positive cell line (MCF-7) were elucidated to identify the potential underlying molecular mechanisms using in silico (molecular docking) and in vitro (cytotoxicity assay, cell cycle analysis, annexin V-FITC apoptosis assay, and reverse transcription and quantitative real time-PCR) techniques as well. Results: The results demonstrated that combined treatment with Con A and TAM reduced the expression of ERα, which showed clear synergistic effects on inhibiting the cell viability of MCF- 7 cells. Interestingly, the combined treatment induces G1 phase arrest and reduces cyclin D1 activity while increasing apoptosis and autophagy as indicated by decreasing the expression level of anti-apoptosis gene BCl-2 and increased apoptosis/autophagic gene BNIP3. Molecular docking was conducted to evaluate the binding affinity of Con A towards ERα, and it revealed its potential activity as an ERα antagonist. Our data further indicated that Con A administration increased the drug reduction index of TAM. Conclusion: Overall, our findings suggested that Con A could be used as an adjuvant agent with TAM to improve its effectiveness as an anticancer agent.